Conversion of a conventional to a digital lecture under the conditions of Covid19 – an example from a bachelor lecture on finishing, dyeing & printing - Boris Mahltig (Communications in Development and Assembling of Textile Products)
Due to the Covid-19 pandemic situation during the years 2020 and 2021, the necessity occurred to convert conventional university lectures into digital ones, to avoid personal contacts between people and by this minimizing the spreading of the disease. Beside lectures, also exams have to be transferred to minimize personal contacts. This paper reports on a lecture in a bachelor course with more than 100 students and its conversion to digital format. The lecture is related to textile finishing processes – especially to dyeing and printing. The experience get during the digital lecture are compared with the results gained during the last decade with the same lecture in conventional style. Main tools of the digital format are video conferences and digital worksheets. Challenging are the contact to students by e-mail and the time management of the students especially during the final digital homework. In conclusion, digital lecture and exam are valuable tools to increase the number of participating students and their success in the exam. These tools could be also used successfully in post-corona times especially for lectures given for experienced students in higher semester.